2013
DOI: 10.3390/ijms14022559
|View full text |Cite
|
Sign up to set email alerts
|

Neurodegeneration and Neuroprotection in Diabetic Retinopathy

Abstract: Diabetic retinopathy is widely considered to be a neurovascular disease. This is in contrast to its previous identity as solely a vascular disease. Early in the disease progression of diabetes, the major cells in the neuronal component of the retina consist of retinal ganglion cells and glial cells, both of which have been found to be compromised. A number of retinal function tests also indicated a functional deficit in diabetic retina, which further supports dysfunction of neuronal cells. As an endocrinologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 83 publications
(98 reference statements)
3
52
0
3
Order By: Relevance
“…Pursuing neuroprotection is therefore a new therapeutic strategy in the treatment of DR [18,19]. Our results show that, following exposition to HG cell culture medium, citicoline reduced apoptosis, as already described in retinal tissue cultures [8], and reversed synapse loss.…”
Section: Resultssupporting
confidence: 78%
“…Pursuing neuroprotection is therefore a new therapeutic strategy in the treatment of DR [18,19]. Our results show that, following exposition to HG cell culture medium, citicoline reduced apoptosis, as already described in retinal tissue cultures [8], and reversed synapse loss.…”
Section: Resultssupporting
confidence: 78%
“…This includes apoptotic cell death, detected in the different layers of the retina, along with metabolic (Ola et al . ) and morphologic (Gastinger et al . ) neurodegenerative retinal changes.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that the influences of ionotropic glutamatergic and GABAergic neurotransmission on the microglial process motility are indirectly mediated, via extracellular ATP which is released from neurons in response to glutamatergic signaling . ATP-induced stimulation of microglia activity may occur early in retinal disease in response to overstimulated glutamatergic transmission which is a main pathogenic factor of neuronal degeneration in many retinal disorders including ischemiaehypoxia, glaucoma, diabetic retinopathy, and inherited photoreceptor degeneration (Martin et al, 2002;Osborne et al, 2004;Delyfer et al, 2005;Ola et al, 2013).…”
Section: Purinergic Regulation Of Microglia Activitymentioning
confidence: 97%